TOTAL FENOL DAN AKTIVITAS ANTIOKSIDAN BUBUK KULIT MANGGIS (Garcinia mangostana L.) DARI BUAH SEGAR DENGAN VARIASI LAMA PENYIMPANAN YANG DIOLAH SECARA MEKANIS - Irwan Roza; Evawati Evawati; Rince Alfia Fadri; Gusmalini Gusmalini (Universitas Andalas, 2017)
This study aims to determine the total content of phenolic compounds and antioxidant activity of mangosteen skin powder from fresh fruit with variations of storage duration which processed mechanically. Methods of research done by determining the total content of phenolic compounds using the method of DPPH free radical scavengers. The fresh mangosteen skin was dried with a drying oven, with a capacity of 0.12 kg/h and a drying rate of 2.79 kg. Furthermore, dry mangosteen skin was milled by grinding machine with 2870 rpm rotation and obtained rendemen mangosteen skin powder as much as 38.04% with water content 8.33%. Total content of phenolic mangosteen powder with variation of storage duration 0 days, 10 days, and 20 days ranged 81.17 mgGAE / g - 195.51 mgGAE /g. The range of IC 50 for the three treatment is 6.80 ppm - 26.47 ppm. The highest total phenolic content and antioxidant activity werw found at zero days of storage.